A Systematic Review of Informal Relationships Among Parents of Individuals With Intellectual Disability or Autism. (September 2016) - Boehm, Thomas L.; Carter, Erik W.
Social relationships can shape the well-being of parents of children with intellectual and developmental disabilities (IDDs). Although much attention has focused on relationships with other family members or professionals, less is known about the place and contributions of informal relationships (i.e., non-family, unpaid others) in the lives of parents. In this review, we synthesize findings from 52 studies addressing the informal relationships of parents and explore their association with a range of parent and family outcomes. We present findings addressing three related relationship dimensions: the affiliations parents report having, their perceptions of these informal relationships, and the supports exchanged within these relationships. This collection of studies incorporated a wide range of measures to characterize these relationships, highlighting the complexities of capturing this aspect of parents' lives. We discuss implications for future research and translating these efforts to improve the lives of parents of children with IDD.